Programma: 27 december: Welcome to the future; 1 januari: Salsa dansavond; 6 januari: Paradiso Talentenshow; 7 januari: Dutch Metal Night (1993)
Programma: 27 december: Welcome to the future; 1 januari: Salsa dansavond; 6 januari: Paradiso Talentenshow; 7 januari: Dutch Metal Night.